The Role of Price in Mediating Product Quality on Purchasing Decisions at Cipadu Market, Tangerang City, Banten Province - Reno Catelya Dira Oktavia; Ismeth Emier Osman; Tri Djoko Sulistiyo; Gratia Wirata Laksmi; Emenina Tarigan (At-Tadbir : jurnal ilmiah manajemen, 2024)
This research aims to determine the role of price in mediating product quality on purchasing decisions at Cipadu Market, Tangerang City. This type of research is descriptive research with a quantitative approach using the path analysis method. The location of this research was at Cipadu Market. The sampling technique used accidental sampling because the researcher happened to meet the respondents directly. The research results show that; (1) Product quality has a significant effect on price; (2) Product quality has a significant effect on purchasing decisions; (3). Price has a significant effect on purchasing decisions. Product quality and affordable prices at Cipadu Market are interrelated, creating an attraction that influences consumer purchasing decisions, with a focus on customer satisfaction and trust, as well as business strategies to maintain low prices without sacrificing quality. Traders are advised to ensure high quality standards, offer a variety of products, collaborate with trusted manufacturers, and maintain competitive prices. Consumers are asked to provide reviews that give merchants insight into product quality and user satisfaction.